Pembelajaran Kolaboratif dalam TEFL: Pendekatan Konstruktivis Sosial Melalui Lensa ZPD - Mohammad Bolad, Mahmoud Amjad; Hateenah Ali Sulaiman Yousef; Khanngeun Vongsawath; Miss Nuro Sabuela; Endang Fauziati (Samudra Publisher, 2025)
This research highlighted the role of collaborative learning in the frame of Teaching English as a Foreign Language (TEFL) within the lens of a social constructivist learning theory, with a specific highlight on the Zone of Proximal Development (ZPD) created by Vygotsky. This study applied a qualitative method, collecting data from a reflective journal and follow-up interviews with four participants involved in a collaborative TEFL-based activity writing an article to gather their insights and experiences while doing so. The results indicated how involvement in critical thinking, peer support, and active participation within a collaborative set, influenced the participants’ English language skills and academic development within the TEFL context. The research contributes to the literature by illustrating the effectiveness of combining ZPD and social constructivist principles in TEFL, providing usable knowledge for educators and policymakers to implement these collaborative techniques that provide in-depth linguistic understanding and more positive learning environment.